ChemInform Abstract: A General Diversified Synthesis of Carbazoles and the First Synthesis of Karapinchamine A. Issue 16 (April 2015) - Qiu, Youai; Zhou, Jing; Fu, Chunling; Ma, Shengming
Abstract The synthetic potential of this Au‐catalyzed propargylic alcohol cyclization reaction is demonstrated in the first synthesis of karapinchamine A (IX).